S1: Marie Byrd Land lithospheric mantle: a review of the xenolith record - Monica R. Handler (8867129); Richard J. Wysoczanski (5771372); John A. Gamble (5771363) (2021)
Analytical methods and literature sources for off-cratonic spinel peridotite whole-rock data